Pediatric Trauma and Trauma Team Activation in a Swiss Pediatric Emergency Department: An Observational Cohort Study - Anouk Herren; Cameron S. Palmer; Markus A. Landolt; Markus Lehner; Thomas J. Neuhaus; Leopold Simma (MDPI AG, 2023)
Background. Trauma is one of the most common causes of death in childhood, but data on severely injured Swiss children are absent from existing national registries. Our aim was to analyze trauma activations and the profiles of critically injured children at a tertiary, non-academic Swiss pediatric emergency department (PED). In the absence of a national pediatric trauma database, this information may help to guide the design of infrastructure, processes within organizations, training, and policies. Methods. A retrospective analysis of pediatric trauma patients in a prospective resuscitation database over a 2-year period. Critically injured trauma patients under the age of 16 years were included. Patients were described with established triage and injury severity scales. Statistical evaluation included logistic regression analysis. Results. A total of 82 patients matched one or more of the study inclusion criteria. The most frequent age group was 12-15 years, and 27% were female. Trauma team activation (TTA) occurred with 49 patients (59.8%). Falls were the most frequent mechanism of injury, both overall and for major trauma. Road-traffic-related injuries had the highest relative risk of major trauma. In the multivariate analysis, patients receiving medicalized transport were more likely to trigger a TTA, but there was no association between TTA and age, gender, or Injury Severity Score (ISS). Nineteen patients (23.2%) sustained major trauma with an ISS > 15. Injuries of Abbreviated Injury Scale severity 3 or greater were most frequent to the head, followed by abdomen, chest, and extremities. The overall mortality rate in the cohort was 2.4%. Conclusions: Major trauma presentations only comprise a small proportion of the total patient load in the PED, and trauma team activation does not correlate with injury severity. Low exposure to high-acuity patients highlights the importance of deliberate learning and simulation for all professionals in the PED. Our findings indicate that high priority should be given to training in the management of severely injured children in the PED. The leading major trauma mechanisms were preventable, which should prompt further efforts in injury prevention.